Alphabears : an ABC book - Hague, Kathleen; Hague, Michael (New York : Henry Holt, 1999)
Each letter of the alphabet is represented by the name of a bear, whose special qualities are described in rhyme.
On board pages.
Keywords: Teddy bears -- Fiction; Toys -- Fiction; Alphabet; Stories in rhyme